(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Dark Energy from the void makes our Universe rotate. The centrifugal force due to the rotation flings galaxies in the outward direction which leads to the experimentally observed accelerated expansion of our Universe. We provide further experimental proof that out Universe is rotating which keeps it from being isotropic and homogeneous, a necessary and sufficient condition for the Cosmological Principle and the introduction of the scale factor a(t), a distance function only of time, while in fact distances measured must be functions of both time and space. This erroneous assumption invalidates all equations within theCosmological Principle that contain a(t) and its derivatives. We point out some of these erroneous equations of the Cosmological Principle which is based on a non-rotating Universe since a Universe that is not rotating violates the Conservation of Angular Momentum Principle. Subatomic particles, atomic nuclei, planets, stars, galaxies, that are all rotating get their rotation from the Angular Momentum of the Universe.